The special librarian in the Metropolitan Manila area a profile - Yabut, Astrida G.; Santos, Herminia H.; Buenaventura, Angeles (Quezon City Institute of Library Science, University of the Philippines Diliman, 1977)
This is a survey of one hundred eighty-nine librarians in one hundred twenty libraries in the Metropolitan Manila area. It is an attempt to arrive at a profile of the special librarians taking into account their personnel characteristics, qualifications, economic status and work experiences, services rendered, interest in professional growth or continuing education and professional activities. It also tries to compare special librarians with public and academic librarians based on materials available at the Institute of Library Science Library, University of the Philippines.
Based on this survey, the typical special librarian generally is described as about thirty-six years old and a family-centered married female. She is a holder of a bachelor's degree (not necessarily in librarianship) and has a variety of other interests especially in terms of recreational activities. In her work, she performs mainly professional duties and to a certain extent is interested in professional growth. She is an active participant in professional association activities.
Typescript.
Vita.
Special Problem (Master of Library Science)
Keywords: Special librarians -- Manila Metropolitan Area